Modeling of Dephosphorization using Bloated Droplet Theory in Basic Oxygen Steelmaking. Issue 1 (19th February 2015) - Ankit,; Kundu, T K
Abstract: A considerable fraction of refining of hot metal in basic oxygen steelmaking is carried out in emulsion layer by interaction between the metal droplets and slag. The top oxygen blowing ejects metal droplets into the slag which then undergo refining reactions and return to the metal bath. During this period, the carbon in metal droplets reacts with available oxygen to form carbon monoxide. Above a certain threshold decarburization rate, the evolved carbon monoxide inside the droplet causes the droplet to bloat which increases its surface area. The bloating affects the residence time and the rate of certain interfacial reactions. Here, efforts have been made to study dephosphorization in metal droplet in emulsion by coupling dephosphorization kinetics with the 'bloated droplet theory'. As observed in industrial furnaces, the calculated phosphorous concentration in droplet was found to be lower than that of metal bath. Dephosphorization model developed using mixed transport control model was found to fit industrial data. The results obtained were in satisfactory agreement with the available data and a step ahead in improving the understanding of dephosphorization in steelmaking.